Design and Construction of Ag@MOFs Immobilized PVDF Ultrafiltration Membranes with Anti-bacterial and Antifouling Properties - Wentao Xu; Huaqiang Zhuang; Zehai Xu; Mianli Huang; Shangchan Gao; Qingbiao Li; Guoliang Zhang (Advances in Polymer Technology)
In this work, Ag nanoparticle loading Mg(C10H16O4)2(H2O)2(Ag@MOF) composite material was successfully prepared by a facile strategy, and subsequently Ag-MOFs were used to modify the PVDF ultrafiltration membranes to obtain fouling resistance and higher water flux. The as-prepared PVDF membranes were systematically characterized by a series of analytical techniques such as Water Contact Angle (CA), Scanning Electron Microscopy (SEM), and SEM-mapping. Furthermore, the performance of membranes on antibacterial properties, the pure water flux, and fouling resistance was investigated in detail. Those results showed that the membrane modified by Ag@MOFs containing 30% Ag had the higher anti-bacterial performance, and the clear zone could be increased to 10 mm in comparison with that of blank membrane. Meanwhile, the pure water flux of Ag@MOF membranes increased from 85 L/m2 h to 157 L/m2 h, and the maximum membrane flux recovery rate (FRR) of 95.7% was obtained using SA as pollutant, which is attributed to the introduction of Ag@MOF composite material. Based on the above experimental results, it can be found that the Ag-MOF membranes displayed the excellent antibacterial activity, high water flux, and fine fouling resistance. This work provides a facile strategy to fabricate the Ag@MOFs modified membranes, and it shows an excellent anti-bacterial and water flux performance.